A preliminary study on the evaluation of left atrial function of rheumatoid arthritis by two dimensional speckle tracking imaging - Xiang Ji (Nature Portfolio, 2021)
Abstract To evaluate the changes of left atrial (LA) geometry and function in patients with rheumatoid arthritis (RA) by conventional echocardiography and two-dimensional speckle tracking imaging (2D-STI). We enrolled 46 RA patients with a duration of < 5 years as Group I, 40 RA patients with a duration of ≥ 5 years as Group II, and 40 normal subjects as the control group. Conventional echocardiography was conducted to measure traditional parameters. The LA strain during reservoir phase (LASr), LA strain during conduit phase (LAScd), LA strain during contraction phase (LASct), and LA global longitudinal strain (LAGLS) were obtained from 2D-STI. Related ultrasound results were compared. The LASct was significantly higher in Group I than in control group (P < 0.05). The LASr, LAScd, and LAGLS were significantly lower in Group I than in control group (all P < 0.05). The LASr, LAScd, LASct, and LAGLS were significantly lower in Group II than in control group and Group I (all P < 0.05). The function of LA impaired in RA patients, and the impairment aggravated with the clinical course of RA patients. 2D-STI technology can early and accurately evaluate the LA function of RA patients by evaluating LASr, LAScd, LASct, and LAGLS.